Workshop Pengumpulan dan Visualisasi Data Online Survei Kepuasan Masyarakat terhadap Pelayanan Puskesmas di Lombok Tengah - Moh Ali; Menap Menap (University of Merdeka Malang, 2021)
Many people feel helped by the health center services and there are also people who are not satisfied. The Community Satisfaction Survey (SKM) was conducted to determine the quality of services provided by community health centers. For government-owned public service providers, the Minister of PANRB issued a regulation on SKM Number 14 of 2017. Based on information from the Head of the Primary Health Care Section of the Central Lombok Regency Health Office in 2019 only 6 puskesmas out of 28 puskesmas conducted a survey but the documents sent did not comply with the guidelines. This is because the puskesmas do not understand the benefits of SKM, have not received socialization, do not yet understand the techniques for conducting SKM and the calculation of survey results. The solution offered in this workshop is to provide knowledge about SKM, about the 9 elements of public service quality that determine satisfaction, providing skills in collecting and visualizing online data from survey results. The results obtained from this activity were an increase in the knowledge and skills of public health centers regarding SKM and the implementation of online data collection and visualization of the Community Satisfaction Survey went well.DOI: https://doi.org/10.26905/abdimas.v6i2.5384